2003
DOI: 10.1016/s0264-410x(03)00362-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individual and combination DNA vaccines for B. anthracis, Ebola virus, Marburg virus and Venezuelan equine encephalitis virus

Abstract: Multiagent DNA vaccines for highly pathogenic organisms offer an attractive approach for preventing naturally occurring or deliberately introduced diseases. Few animal studies have compared the feasibility of combining unrelated gene vaccines. Here, we demonstrate that DNA vaccines to four dissimilar pathogens that are known biowarfare agents, Bacillus anthracis, Ebola (EBOV), Marburg (MARV), and Venezuelan equine encephalitis virus (VEEV), can elicit protective immunity in relevant animal models. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 49 publications
3
86
1
Order By: Relevance
“…Put most simply, higher doses of vaccine seem to evoke greater total immune responses, along with a protection that is more rapidly acquired and more complete than that obtained with replication-defective vaccines given at much lower doses. A recent report with a recombinant adenovirus that expresses the ZEBOV glycoprotein, in which the minimal protective dose of 10 10 particles is described as a 'low dose' , affirms that protection is dependent on the vaccine dose 65 , and might explain why repliconbased vaccines given at much lower doses have not been uniformly successful 67 and DNA vaccines have been only partially effective 79 . Live vesicular stomatitis virus (VSV) 64 or parainfluenza virus 80,81 recombinants, which show considerable promise in protecting non-human primates from filoviral infection, presumably generate high amounts of viral glycoprotein antigen in vivo.…”
Section: Cellular Immunity To Filovirus Infectionmentioning
confidence: 99%
“…Put most simply, higher doses of vaccine seem to evoke greater total immune responses, along with a protection that is more rapidly acquired and more complete than that obtained with replication-defective vaccines given at much lower doses. A recent report with a recombinant adenovirus that expresses the ZEBOV glycoprotein, in which the minimal protective dose of 10 10 particles is described as a 'low dose' , affirms that protection is dependent on the vaccine dose 65 , and might explain why repliconbased vaccines given at much lower doses have not been uniformly successful 67 and DNA vaccines have been only partially effective 79 . Live vesicular stomatitis virus (VSV) 64 or parainfluenza virus 80,81 recombinants, which show considerable promise in protecting non-human primates from filoviral infection, presumably generate high amounts of viral glycoprotein antigen in vivo.…”
Section: Cellular Immunity To Filovirus Infectionmentioning
confidence: 99%
“…[17][18][19][20][21] In earlier studies, we showed that DNA vaccines expressing the GP genes of MARV delivered by gene gun elicited partially protective immunity in NHP. 22 Similarly, we showed that an EBOV GP DNA vaccine delivered to guinea pigs by gene gun provided partial protection against EBOV challenge. 23 Toward the goal of improving the protective efficacy of these DNA vaccines, we designed gene-optimized DNA vaccine constructs and used a more potent delivery method, intramuscular electroporation (IM-EP).…”
Section: Introductionmentioning
confidence: 79%
“…22 We also tested a similar EBOV DNA vaccine, using a prime-boost regimen with a DNA prime and a baculovirus-expressed EBOV GP boost. Although this approach was successful for MARV in guinea pigs and nonhuman primates (NHP), it was not successful for conferring protective immunity against EBOV.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, a DNA vaccine expressing MARV GP was weakly immunogenic compared to other strategies and offered incomplete protection when given alone but worked well when boosted with baculovirus-expressed GP TM [60]. In NHP, the DNA MARV GP vaccine protected four of six cynomolgus macaques from lethal MARV infection [80]. In mice, a DNA vaccine expressing GP from ZEBOV was able to fully protect mice against ZEBOV challenge [80] but failed to adequately protect guinea pigs [79].…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…In NHP, the DNA MARV GP vaccine protected four of six cynomolgus macaques from lethal MARV infection [80]. In mice, a DNA vaccine expressing GP from ZEBOV was able to fully protect mice against ZEBOV challenge [80] but failed to adequately protect guinea pigs [79]. Another DNA vaccine construct, however, was successful in protecting guinea pigs against ZEBOV challenge [81].…”
Section: Dna Vaccinesmentioning
confidence: 99%